2003
DOI: 10.1523/jneurosci.23-08-03295.2003
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Magnetic Resonance Imaging Studies of Older Adults: A Shrinking Brain

Abstract: Age-related loss of brain tissue has been inferred from cross-sectional neuroimaging studies, but direct measurements of gray and white matter changes from longitudinal studies are lacking. We quantified longitudinal magnetic resonance imaging (MRI) scans of 92 nondemented older adults (age 59-85 years at baseline) in the Baltimore Longitudinal Study of Aging to determine the rates and regional distribution of gray and white matter tissue loss in older adults. Using images from baseline, 2 year, and 4 year fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

80
953
13
11

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,240 publications
(1,057 citation statements)
references
References 38 publications
80
953
13
11
Order By: Relevance
“…However, volumes of other regions in the brain also show sex differences. Some imaging studies have reported age‐differences in the function of the parietal cortex and an increased sensitivity of the parietal lobe to the aging‐driven brain atrophy (Jacobs et al., 2011; Resnick, Pham, Kraut, Zonderman, & Davatzikos, 2003). Thus, parietal GM may be a brain region where the involvement of SHBG in both sex hormone and metabolic pathways converge in men.…”
Section: Discussionmentioning
confidence: 99%
“…However, volumes of other regions in the brain also show sex differences. Some imaging studies have reported age‐differences in the function of the parietal cortex and an increased sensitivity of the parietal lobe to the aging‐driven brain atrophy (Jacobs et al., 2011; Resnick, Pham, Kraut, Zonderman, & Davatzikos, 2003). Thus, parietal GM may be a brain region where the involvement of SHBG in both sex hormone and metabolic pathways converge in men.…”
Section: Discussionmentioning
confidence: 99%
“…The Baltimore Longitudinal Study reported age-related changes in MRIderived signal intensity, which was believed to reflect demyelination and changes in water, protein, and mineral content in the old (Davatzikos and Resnick 2002). Results from the same study also reported that while WM volume was stable after 1 year in old subjects (Resnick et al 2000), it decreased regionally and globally after 4 years (Resnick et al 2003), suggestive that a critical age threshold was achieved. Functionally, longitudinal studies have shown WM atrophy in the CC of elderly men is associated with cognitive dysfunction (Sullivan et al 2002).…”
Section: Longitudinal Imaging Studies In Humansmentioning
confidence: 91%
“…Voxel-based morphometry has also been used to evaluate voxel-by-voxel brain changes in healthy aging (Resnick, Pham et al 2003), AD (Ashburner, Csernansky et al 2003), and FTD (Rosen, Gorno-Tempini et al 2002;Grossman, McMillan et al 2004;Whitewell, Josephs et al 2005). These studies have confirmed patterns of atrophy that predominantly involve medial temporal lobe structures in subjects with mild cognitive impairment and patients with AD, and frontal and temporal regions in patients with FTD or AD, albeit the fronto-temporal atrophy in AD is part of a more widespread pattern of atrophy.…”
Section: Introductionmentioning
confidence: 89%
“…Structural MRI has the potential to both aid diagnosis and provide objective surrogate markers of effects of pharmacological interventions designed to slow or halt the neurodegenerative process. Advanced image analysis methodologies have also been described in the literature, aiming to quantify structural characteristics of healthy individuals and patients with AD or FTD (Thompson, Mega et al 2001;Resnick, Pham et al 2003;Fox and Schott 2004;Grossman, McMillan et al 2004;Chang, Lomen-Hoerth et al 2005;Likeman, Anderson et al 2005;Short, Broderick et al 2005;Barnes, Whitwell et al 2006).…”
Section: Introductionmentioning
confidence: 99%